Actual veterinary and medical terms as the representers of anatomical nomenclature (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The structural organization of anatomical terms is considered in the article; the potential compatibility quality of veterinary and medical terms and the types of logical ties between them are analyzed.
Keywords: universal worldview; terminological standards; terminological code; anatomical nomenclature; veterinary medicine terms; monocomponent and polycomponent terms